(untitled) (CIPEEX, 2025)
The objective of this study is to investigate the profile of children and adolescents who are victims of exploitation through child labor in Brazil. Considering that child labor is a permanent reality in the country, through the methodology of bibliographical review and analysis of data from official bodies, it was possible to identify the predominant characteristics of children and adolescents currently working. It must be considered that the presence of children in the labor market is not recent, considering that since the colonial period there had been exploitation of child labor, especially as a result of the slavery regime. With the Industrial Revolution, children and adolescents became present in factories, as they represented cheap labor without great needs. Currently, poverty is directly related to this type of work, as children and adolescents between the ages of 5 and 17 work to help make up the family income. According to IBGE, in 2022, 1.9 million children and adolescents in the age group mentioned above were working. In this number, boys predominate over girls and blacks exceed the number among whites. Considering the activities, it was found that many work informally and girls’ income is lower than that of boys. It was possible to conclude that the situation is still alarming and requires an assertive stance from public authorities to combat this exploitation, whether with stricter laws or the implementation of Public Policies to serve low-income families with the aim of removing children and adolescents from work.